Performance Bounds of DPSK and OOK for Low Elevation Optical LEO Downlinks - Henniger, Hennes; Ludwig, Alexandra; Horwath, Joachim (Společnost pro radioelektronické inženýrství, 2010)
Optical wireless LEO downlinks are seen as an emerging solution to increase available bandwidth to multigigabits per second. One of the biggest challenges is the impact of the atmosphere on the optical signal. The atmosphere causes time-varying link degradation due to index of refraction turbulence, especially at low elevation angles. Since the influence of the turbulence for low elevation downlinks is hardly investigated we perform numerical propagation simulations in order to achieve reliable received signal statistics. These results are further utilized to evaluate performance bounds of optical wireless systems from an information theory perspective. We focus on the two most common optical wireless systems, i.e. NRZ-DPSK and NRZ-OOK. This work shows that under low elevation angles acceptable quality of service can only be reached with high code rates.
Keywords: Free-space optical communications; channel capacity; index of refraction turbulence; fading; LEO downlink; system performance